We didn't know it was impossible! a history of the University of Albuquerque Theatre Department - Morley, Jim; Gilbert, Susanna; Johnson, Barbara (Albuquerque, N.M. University of New Mexico, General Library, Center for Southwest Research, 1991)
Oral history of the University of Albuquerque theatre Jim Morley, Director
"May 19, 1991."
112129
Keywords: Morley, Jim -- Interviews; University of Albuquerque. -- Theatre Department -- History; Theater -- New Mexico -- Albuquerque; Theater; New Mexico -- Albuquerque; History; Interviews